Pengembangan Website Company Profile Menggunakan Codeigniter Untuk Mendukung Branding Perusahaan - Hamdun Sulaiman; Kukuh Panggalih; Yuri Yuliani; Kudiantoro Widianto; Irwan Herliawan (Fakultas Teknik Universitas Hamzanwadi, 2026)
A company profile website is a digital medium used by companies to effectively convey information about their profiles, services, and portfolios to the public. In the era of digital transformation, the existence of a website is crucial because it can increase a company's visibility, credibility, and competitiveness. This study aims to design and develop a CodeIgniter 3-based company profile website that adapts to user needs and facilitates content management. Needs analysis was conducted through observation and interviews, while the system design utilizes UML and a responsive interface design that supports various devices. The implementation used PHP with the CodeIgniter 3 framework and a MySQL database. The results show that the website is capable of displaying profile information, services, portfolios, blogs, and contacts, as well as providing a simple CMS for independent content updates. In conclusion, this website can enhance professionalism, strengthen branding, and simplify the management of company information. Further developments could include social media integration, SEO optimization, multi-language support, and visitor analytics features. Additional security features and performance enhancements could also be considered to ensure the system's sustainable quality and reliability in the future.